Performance of space time block coding in an IEEE 802.16-2004 OFDM physical link / Nurul Hidaya Mustafa Al Bakri - Mustafa Al Bakri, Nurul Hidaya
This paper highlights the performance of Space Time Block Coding in an IEEE 802.16-2004 OFDM physical link. The evaluation was done by comparing the performance of the system which include Space Time Block Coding and with the system that exclude the Space Time Block Coding. The system parameters that were used in this study were the cyclic prefix (CP) factor which is 1/4, 1/8/, 1/16, 1/32 and a range of SNR which is -10 to 10. BER is evaluated from these parameters and compared between the two systems. This study has been done using MATLAB 7.5.0 (R2007b). The finding shows that the BER value is lowest in the system which has the Space Time Block Coding (STBC). Overall, it shows that with Space Time Block Coding, the performance of Wireless System is better by 99.97% with a cyclic prefix at 1/32.